2022
DOI: 10.5114/fn.2021.112567
|View full text |Cite
|
Sign up to set email alerts
|

Iduna contributes to the therapeutic effect of DHA in a cell and mouse model of traumatic brain injury via Wnt/MDM2 pathway

Abstract: Traumatic brain injury (TBI) is a severe condition that leads to brain damage and affects brain function. Importantly, TBI incurs public health costs due to its high mortality, and effective treatment for TBI is still lacking. Docosahexaenoic acid (DHA) has a neuroprotective effect that can reduce oxidative, apoptosis, and inflammatory processes. Administration of DHA after TBI attenuates oxidative stress and protein accumulation and is regarded as a potential therapeutic. Iduna is a regulator of parthanatos, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Recent studies demonstrated that iduna is a newly discovered ubiquitin E3 ligase and an endogenous regulator of parthanatos, which can reduce PARP activation and nuclear translocation of AIF to prevent parthanatos, indicating that ubiquitin-proteasome pathway may also play a role in parthanatos (Xu et al, 2019). At the same time, iduna may promote docosahexaenoic acid 10.3389/fnmol.2022.1005422 (DHA) through Wnt/MDM2 pathway and reduce the damage of TBI cell and mitochondrial dysfunction (Shi et al, 2022). Based on these reports, targeting PARP1-dependent parthanatos may be a potential strategy for the treatment of secondary injury after TBI.…”
Section: The Parthanatos Involved In Traumatic Brain Injurymentioning
confidence: 99%
“…Recent studies demonstrated that iduna is a newly discovered ubiquitin E3 ligase and an endogenous regulator of parthanatos, which can reduce PARP activation and nuclear translocation of AIF to prevent parthanatos, indicating that ubiquitin-proteasome pathway may also play a role in parthanatos (Xu et al, 2019). At the same time, iduna may promote docosahexaenoic acid 10.3389/fnmol.2022.1005422 (DHA) through Wnt/MDM2 pathway and reduce the damage of TBI cell and mitochondrial dysfunction (Shi et al, 2022). Based on these reports, targeting PARP1-dependent parthanatos may be a potential strategy for the treatment of secondary injury after TBI.…”
Section: The Parthanatos Involved In Traumatic Brain Injurymentioning
confidence: 99%